2022
DOI: 10.3389/fpls.2022.1079180
|View full text |Cite
|
Sign up to set email alerts
|

The stimulatory effect of Thuricin 17, a PGPR-produced bacteriocin, on canola (Brassica, napus L.) germination and vegetative growth under stressful temperatures

Abstract: Exposure to unfavorable conditions is becoming more frequent for plants due to climate change, posing a threat to global food security. Stressful temperature, as a major environmental factor, adversely affects plant growth and development, and consequently agricultural production. Hence, development of sustainable approaches to assist plants in dealing with environmental challenges is of great importance. Compatible plant-microbe interactions and signal molecules produced within these interactions, such as bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…A similar conclusion, distinct responses to different concentrations of bacterial compounds, was reached by other studies (Schwinghamer et al, 2015(Schwinghamer et al, , 2016Naamala et al, 2022). A clear example of this was observed in our previous study when three different concentrations of Th17, 10 −7 , 10 −9 , and 10 −11 M, were applied, and nanomolar of Th17 was the most effective in enhancing seed germination, seedling growth, and vegetative growth under stressfully high temperatures (Nazari et al, 2022). Our findings are consistent with the work of Schwinghamer et al (2016) regarding the application of different levels of two microbial compounds, LCO and Th17, which indicated concentration-dependent behavioral responses under various growth conditions and development stages.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…A similar conclusion, distinct responses to different concentrations of bacterial compounds, was reached by other studies (Schwinghamer et al, 2015(Schwinghamer et al, , 2016Naamala et al, 2022). A clear example of this was observed in our previous study when three different concentrations of Th17, 10 −7 , 10 −9 , and 10 −11 M, were applied, and nanomolar of Th17 was the most effective in enhancing seed germination, seedling growth, and vegetative growth under stressfully high temperatures (Nazari et al, 2022). Our findings are consistent with the work of Schwinghamer et al (2016) regarding the application of different levels of two microbial compounds, LCO and Th17, which indicated concentration-dependent behavioral responses under various growth conditions and development stages.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, for foliar experiments, across all conditions, no meaningful changes were observed due to the application of the compound. Our previous studies have indicated positive effects of treating canola seeds and root drenching with 10 −9 and 10 −11 M Th17, which caused germination increases, germination time reduction, and longer radicals under moderately high temperature and optimal conditions (Nazari et al, 2022). Similar root development effects on soybean have been reported for this plant growth regulator under salt stress and this was associated with changes in the level of ABA (Prudent et al, 2015).…”
Section: Changes In the Root Systemmentioning
confidence: 56%
See 3 more Smart Citations